1998
DOI: 10.1139/x98-012
|View full text |Cite
|
Sign up to set email alerts
|

Parental environment aftereffects on germination, growth, and adaptive traits in selected white spruce families

Abstract: Seed orchards for the production of conifer seed in British Columbia are usually located in areas favorable (warm and dry) for flowering and seed development, often considerably south of the source location of the parent trees. Differences in environmental conditions between seed orchard location and location of origin can affect progeny performance. It is suspected that this is caused by environmental factors that affect reproductive processes of parent trees and lead to altered physiological traits (aftereff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 17 publications
(25 reference statements)
4
17
0
Order By: Relevance
“…Some authors only found effects of the maternal environment (for example, Galloway et al, 2009), whereas others have found the opposite (for example, Halpern, 2005). Most frequently, however, both factors have been found to significantly affect mean SM (for example, Stoehr et al, 1998;Elwell et al, 2011). Our results agree with these studies, and clearly show a strong genetic component in SM as well as a large influence of the maternal environment (Table 2, Figure 1).…”
Section: Sm Variationsupporting
confidence: 90%
See 1 more Smart Citation
“…Some authors only found effects of the maternal environment (for example, Galloway et al, 2009), whereas others have found the opposite (for example, Halpern, 2005). Most frequently, however, both factors have been found to significantly affect mean SM (for example, Stoehr et al, 1998;Elwell et al, 2011). Our results agree with these studies, and clearly show a strong genetic component in SM as well as a large influence of the maternal environment (Table 2, Figure 1).…”
Section: Sm Variationsupporting
confidence: 90%
“…Further research analysing parent-offspring regression and/or family trials should determine the amount of additive variation within the observed genetic variation in SM in this pine species. Because SM has a relevant role in many important life history processes, many studies have focussed on determining the sources of SM variation in different plant species, but the effects of the maternal environment and the maternal genotype have not always been adequately separated (Blodner et al, 2007;Guo et al, 2010), and when they have been separated (Halpern, 2005;Galloway et al, 2009;House et al, 2010), they have usually referred to annual plants (but see Stoehr et al, 1998). Results are very variable.…”
Section: Sm Variationmentioning
confidence: 99%
“…It appeared that the seeds produced in southern seed orchards 'remember' in some way the climate at the site of production, despite containing genes inherited from parents originating from the North (hence the designation 'memory' or 'carryover' effects). Similar observations were made on North-American conifers (Greenwood and Hutchison 1996;Stoehr et al 1998;Webber et al 2005).…”
Section: Uncommon Trait Inheritance In Treessupporting
confidence: 76%
“…There are few such studies in long-lived forest trees, but an example include the demonstration of "seed after-effects" whereby the environment experienced by parents and developing seeds in a tree seed orchard may affect the expression of phenotypic variation in the subsequent deployment population (Andersson 1994;Stoehr et al 1998). Few studies allow the separation of maternal embryonic nuclear and maternal effects (Rasanen and Kruuk 2007;Monty et al 2009;Bischoff and Muller-Scharer 2010), particularly in the case of forest trees (Besnard et al 2008).…”
Section: Introductionmentioning
confidence: 99%